2016
DOI: 10.4172/pharmaceutical-sciences.1000160
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Brassica sprouts for its Antioxidant and Antiproliferative Potential

Abstract: Chaudhary, et al.: In vitro Evaluation of Brassica SproutsThe present study was conducted on sprouts (5 and 7 days) of turnip (Brassica rapa), cauliflower (Brassica oleracea) and mustard (Brassica juncea) for bioactivity. Their antioxidant potential was assessed by 2,2-diphenyl-1-picrylhydrazyl, superoxide anion radical scavenging assays at 0.125-2 mg/ml concentration. The extract of turnip, cauliflower and mustard (5 and 7 days) showed a potent antioxidant effect and significant cytotoxic effect at 100 µg/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…The results are also consistent with the antiproliferative effect described for sulforaphane (15 µM for 24h), an isothiocyanate present in all BFs of microgreens, which produced an increase in sub-G1 and G2/M phases in HT-29 colon cancer cells [28]. Moreover, these results are also in agreement with the increase in sub-G1 and G2/M arrest phases in prostate cancer cells (PC-3), as induced by mustard (Brassica juncea) sprout extracts (10-100 µg/mL) after 12h treatment [29]. Accordingly, these studies suggest that an increase in the G2/M phase, induced by the specific combinations of antioxidant bioactive compounds present in the microgreen BFs, could be a preceding event to apoptosis in tumor cells.…”
Section: Cell Cycle Analysismentioning
confidence: 55%
See 1 more Smart Citation
“…The results are also consistent with the antiproliferative effect described for sulforaphane (15 µM for 24h), an isothiocyanate present in all BFs of microgreens, which produced an increase in sub-G1 and G2/M phases in HT-29 colon cancer cells [28]. Moreover, these results are also in agreement with the increase in sub-G1 and G2/M arrest phases in prostate cancer cells (PC-3), as induced by mustard (Brassica juncea) sprout extracts (10-100 µg/mL) after 12h treatment [29]. Accordingly, these studies suggest that an increase in the G2/M phase, induced by the specific combinations of antioxidant bioactive compounds present in the microgreen BFs, could be a preceding event to apoptosis in tumor cells.…”
Section: Cell Cycle Analysismentioning
confidence: 55%
“…Antioxidants 2020, 9, 368 9 of 15 [29]. Accordingly, these studies suggest that an increase in the G 2 /M phase, induced by the specific combinations of antioxidant bioactive compounds present in the microgreen BFs, could be a preceding event to apoptosis in tumor cells.…”
Section: Cell Cycle Analysismentioning
confidence: 85%
“…Generally, cruciferous vegetables are consumed for their health-promoting benefits, including antioxidant, anti-proliferative, and chemo-preventive activities contributed mainly by GLs and phenolics [ 24 , 68 , 69 , 70 ]. Currently, there are growing pieces of evidence suggesting that oxidative stress from reactive oxidants plays a key role in the pathogenesis of several diseases [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with tubers and flower buds, leaves were revealed with beneficial effects based on the fact that the aqueous extract of fresh turnip leaves showed protective efficiency against genotoxicity and oxidative stress in vivo (Tiku, Abraham, & Kale, ). Turnip sprouts exhibited higher DPPH free radical scavenging activity compared to cauliflower and mustard sprouts (Chaudhary et al., ). Thus, it is concluded that most of antioxidant activities are found in the polar part of turnip, and flower buds are most likely to furnish active compounds for antioxidant purposes.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Two nitrogen compounds, 2‐phenylethyl isothiocyanate ( 21 ) and 3‐phenylpropionitrile ( 92 ), from turnip seed oil, were revealed as potential inhibitors of DNA oxidative damage and mutagens (Robin, Arora, & Vig, ). Moreover, turnip sprout extract was found to exhibit higher antiproliferative activity in a cancerous cell line assay than that of cauliflower and mustard (Chaudhary et al., ). Isothiocyanates and indoles are two types of glucosinolate breakdown products with known anti‐cancer properties (Zhang, Kensler, Cho, Posner, & Talalay, ), of which isothiocyanates can induce apoptosis in various cancer cell lines (Hong & Kim, ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%